Triterpenes and steroids from the leaves of Aglaia exima (Meliaceae) - Leong, K.H. (Elsevier, 2012)
A study on the leaves of Aglaia exima led to the isolation of one new and seven known compounds: six triterpenoids and two steroids. Their structures were elucidated and analyzed mainly by using spectroscopic methods; 1D and 2D NMR, mass spectrometry, UV spectrometry and X-ray. All the triterpenoids and steroids were measured in vitro for their cytotoxic activities against eight cancer cell lines; lung (A549), prostate (DU-145), skin (SK-MEL-5), pancreatic (BxPC-3), liver (Hep G2), colon (HT-29), breast (MCF-7) and (MDA-MB-231). The new cycloartane triterpenoid, 24(E)-cycloart-24-ene-26-ol-3-one 1, showed potent cytotoxic activity against colon (HT-29) cancer cell line (IC50 11.5 μM).